Requirements and Policies for Managing Villages in Tehran Metropolitan Area - Mohammadamin Khorasani (Salehan Institute of Higher Education, 2018)
Due to the spatial proximity to and spatial-physical dependence on cities, the villages of the cities have many facilities, constraints, opportunities and challenges that are not so extreme in other villages. The main objective of this research is to identify the features of villages located in the metropolitan areas of Iran and provide strategies for managing the problems and challenges of these villages, with emphasis on the villages of Tehran Metropolitan Area. The most important policy recommendations presented in this study are: considering an efficient public transportation system for servicing these villages; a strategic look of the municipality's collection on the issue of employment of people in the city villages which are increasingly migrating into Tehran to provide their livelihoods; the issue of green space in the metropolitan villages and their perspective, which is directly available to the villagers, but the municipality of Tehran can take steps in order to improve the indices related to green space and rural landscape in city areas by adopting due measures; Development of an intermediate facility in Tehran with the aim of preventing the city from spreading to the surrounding area and the villages therein; and finally, regionalism's strategy as the most reasonable, operational and efficient management strategy for investigating and managing the challenges of Tehran metropolitan area villages.